O sapato é um martelo: usos e apropriações das novas tecnologias de informação e comunicação por professores da rede pública de ensino - Albuquerque, Ives Manuel de Carvalho (2010)
Our objective here is to analyze how is the relationship of public school teachers with the New Technologies of Information and Communication (NTIC) in their daily activities and what do they retain from them in their educational efforts. To do so, we selected from the application of 21 questionaires, 13 teachers whom were interviewed. These teachers were from two municipality public schools in the cities of Fortaleza and Maracanaú. The research has shown that these teachers perceive a significant change between their generation and that of the adolescent students, because of the new informational and communications technologies. These teachers also identified that their efforts at school is permeated by behavioral and structural problems and they consider the new technologies as influencing or enabling factors for many of these problems. Technology, today, has a constitutive dimension in the contemporary society, defined by Martin-Barbero as the “world-technicity”. This makes social spaces, such as the school, tense and with new meanings. We also noted, however, that the insertion of these NTICs in the school space is not processed in a passive way, where order and silence would prevail. Instead it integrates itself in an intense negotiation movement, with ruptures, distances and closures that, good or bad, have the potential to provoke a new elaboration of the space of the school. We categorize the TICs by the establishment of what we call the sensuous-relational experience which happens with the communicating subject, and therefore we define four levels of TIC: present, teleactive, interactive and immersive. Based on this definition, as we analyzed the space of the school, inside and out of it, we identified that there were profound differences that occurred in the insertion of the TICs in the life of teachers. We also identified that the dynamics developed with these new technologies articulate several interaction ways between teacher and student, even when it comes to the TIC analyzed. We therefore were able to conclude that the communication media are not the only defining factors of the educational experience developed inside the classroom. The way teachers understand the possibilities of the NTIC influences the communication flows in different senses and intensities operating in the classroom. The conditions that allow us to understand these possibilities are directly related to the comprehension that the teachers have their social aspects molded by the NTICs in the contemporaneous society, besides their own perceptions of the school and of education, this way having a deep understanding or not of these new ways of being in their own lives. We therefore came to the conclusion that there are two ways of interactions that involve the teachers with the TIC: the interaction by appropriation of the TIC and that by the use of the TIC. When the teacher appropriates the NTIC, he or she can perceive the changes made by the new technologies and, therefore, make these technologies their own, and their schooling environment’s also. In the case of interaction by use of the NTICs, teachers clearly develop a functionalist and technicist discourse for the use of these communications media in their educational practice, generally linked to the imagery appeal that they provoke in the students, or the instrumental enabling that they make possible in the content of studies, without exploring, in a broader way, their communicational possibilities.